1992
DOI: 10.1002/1097-0142(19920715)70:2<437::aid-cncr2820700211>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metastasis of lung cancer. A study of metastatic pathways and clinical manifestations

Abstract: Background. Although lung cancer frequently spreads to the heart, details of cardiac metastases of lung cancer have not been fully discussed. The authors attempted to elucidate the relationship between the mechanisms of cardiac metastasis and a variety of clinical manifestations caused by cardiac metastasis. Methods. Clinical and autopsy records were reviewed in 74 autopsied cases of lung cancer. In cases with cardiac metastasis, the metastatic pathways to the heart were determined by the macroscopic examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 18 publications
0
47
0
1
Order By: Relevance
“…8) Tamura, et al reported a high incidence (35%) of concurrent supraventricular arrhythmia including PSVT (8%) in their series. 10) Although PSVT was not proved to be related to myocardial invasion in this case, it was reasonably suspected in this elderly patient. Only Yao, et al reported a similar case that presented with both ST-elevation and PSVT.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…8) Tamura, et al reported a high incidence (35%) of concurrent supraventricular arrhythmia including PSVT (8%) in their series. 10) Although PSVT was not proved to be related to myocardial invasion in this case, it was reasonably suspected in this elderly patient. Only Yao, et al reported a similar case that presented with both ST-elevation and PSVT.…”
Section: Discussionmentioning
confidence: 70%
“…6,7) An autopsy series determined that the incidence of cardiac metastasis in patients with malignant disease was as high as 22-31%. [8][9][10] Cardiac metastases, however, are difficult to diagnose before death, because there are frequently few typical signs that are indicative of cardiac metastasis and these signs are often clinically unapparent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to study conducted by Tamura et al the incidence of cardiac & pericardiac metastases in patients with bronchogenic carcinoma was 17 to 31 % [9]. Only few cases of cardiac metastasis from bronchogenic carcinoma via…”
Section: Discussionmentioning
confidence: 99%
“…The heart or the pericardium may be affected in 20% of the cases either directly from tumor infiltration or indirectly because of lymphocytic or hematogenous metastases. Malignant pericardial effusion can be often in lymphatic spread of the tumor (33,40). Arrhythmias can also been present (40,41), while myocardial infarction has also been diagnosed as a result of the compression of the coronary arteries (40).…”
Section: Symptomatologymentioning
confidence: 99%